PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH, MUSYARAKAH, TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH YANG TERDAFTAR DI OJK TAHUN 2019-2022 - Oktariani, Nia (P3M STIE Mulia Darma Pratama, 2024)
Profitability is a profitability ratio used to assess a company's ability to generate profits and demonstrate the efficiency of a Sharia commercial bank in increasing murabahah, mudharabah, and musyarakah financing, thus enabling the profitability of the Sharia commercial bank to improve. This is evident from the fluctuating financial performance, which serves as a reference for banks to be more selective in case of delays in payments related to murabahah, mudharabah, and musyarakah financing. The level of profitability is determined by the profit generated from each of these financing types. The purpose of this research is to examine the development of murabahah, mudharabah, and musyarakah financing on the profitability of Sharia commercial banks registered with the Financial Services Authority (FSA) from 2019 to 2022, and to determine the partial and simultaneous effects of murabahah, mudharabah, and musyarakah financing on profitability in Sharia commercial banks registered with the FSA from 2019 to 2022. This research uses a quantitative research method, and this study was conducted at Sharia commercial banks registered with the FSA. The sampling technique employed is purposive sampling, resulting in 8 samples. Data analysis is conducted using descriptive and verification methods, including multiple linear regression analysis, t-tests, f-tests, and coefficient of determination tests. Based on the partial testing results, it can be concluded that murabahah financing does not significantly affect profitability, whereas mudharabah financing has a significant impact on profitability. However, musyarakah financing does not significantly affect profitability. Simultaneous testing results suggest that at least one independent variable influences profitability.